Answer:
3 − m = −2 (m + 6); m = −15 Yes
5 (p + 3) = −35; p = −4 No
8q = 3 (10 + q); q = 6 Yes
Step-by-step explanation:
3 − m = −2 (m + 6)
3 - m = -2m - 12
m = -15
Answer is Yes
5 (p + 3) = −35
5p + 15 = -35
5p = - 50
p = -10
Answer is No
8q = 3 (10 + q)
8q = 30 + 3q
5q = 30
q = 6
Answer is Yes
Answer:
these are two answers i got
-14=
-5=
Answer:
BE=AD
Step-by-step explanation:
Answer:
![9](https://tex.z-dn.net/?f=9)
Step-by-step explanation:
![f(x) = (x - 2)^{2} \\ f(5) = (5 - 2)^{2} \\ f(5) = {(3)}^{2} \\ f(5) = 3 \times 3 \\ f(5) = 9](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x%20-%202%29%5E%7B2%7D%20%20%5C%5C%20f%285%29%20%3D%20%285%20-%202%29%5E%7B2%7D%20%20%5C%5C%20f%285%29%20%3D%20%20%7B%283%29%7D%5E%7B2%7D%20%5C%5C%20f%285%29%20%3D%203%20%5Ctimes%203%20%5C%5C%20f%285%29%20%3D%209)